2020
DOI: 10.12659/aot.920288
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Serum Lactate Levels for In-Hospital Mortality Prediction Among Heart Transplant Recipients

Abstract: Background:Hyperlactatemia is a common phenomenon following cardiac surgeries and is associated with prolonged ICU stay and higher morbidity and mortality rates, but such analyses have never focused on patients undergoing heart transplantation (HTX), in whom hyperlactatemia defined with the traditional threshold is observed in nearly every individual. The present study aimed to assess the prognostic value and clinical usefulness of postoperative serum lactate level measurements for in-hospital mortality predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…It is positively correlated with the prognosis and mortality of patients with heart failure (11,12). Previous clinical investigation showed that serum lactate levels in heart transplant recipient survivors are significantly lower than those in nonsurvivors, indicating that serum lactate level can be used as a biomarker to determine heart transplant recipient mortality (34). In accordance, Zymlinski et al (11) observed elevated lactate levels in acute heart failure patients, which is associated with damage to the myocardium, liver, and kidney and a higher mortality rate.…”
Section: Discussionmentioning
confidence: 99%
“…It is positively correlated with the prognosis and mortality of patients with heart failure (11,12). Previous clinical investigation showed that serum lactate levels in heart transplant recipient survivors are significantly lower than those in nonsurvivors, indicating that serum lactate level can be used as a biomarker to determine heart transplant recipient mortality (34). In accordance, Zymlinski et al (11) observed elevated lactate levels in acute heart failure patients, which is associated with damage to the myocardium, liver, and kidney and a higher mortality rate.…”
Section: Discussionmentioning
confidence: 99%
“…In the examination of mortality factors, the singular factor correlated with postoperative 60-day death was lactate levels. Elevated lactate levels have been consistently reported as a robust risk factor linked to increased mortality in patients experiencing septic shock, cardiac arrest, hemorrhagic shock, and major surgeries (36)(37)(38)(39). A lactate level of ≥2.5 mmol/L has been identified as the optimal threshold for predicting 28-day mortality in severe sepsis and septic shock patients (40).…”
Section: Discussionmentioning
confidence: 99%
“…408 In the context of endstage cardiac events, specifically heart failure, the level of lactate in the serum is closely associated with the prognosis and mortality of heart failure patients or post-heart transplant recipients. 255,409,410 Furthermore, lactic acid was found to induce myofibroblast differentiation where HIF-2α in lung vascular endothelial cells could pathogenically upregulate SNAIL1/2 and subsequent EndoMT, contributing to vascular remodeling, obliterative pulmonary vascular lesions, pulmonary fibrosis and advancement of severe pulmonary hypertension. 411,412 In addition, EndoMT also plays a vital role in the development of various cardiovascular conditions, including myocardial infarction, atherosclerosis, cardiac fibrosis, and valvular diseases.…”
Section: Intracellular Interactions and Remote Regulations Of Hypoxia...mentioning
confidence: 99%